BomberKaboom: An Educational Game for Environmental Awareness Through Classic Mechanics - Ferreira, Vitor; Nunes, João; Oliveira, Anna; Cassiano, Saymon; Félix, Juliana; Nascimento, Thamer Horbylon; Soares, Fabrizzio (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Environmental awareness is an urgent topic, especially among younger generations. The use of digital games in educational contexts has proven effective in engaging students and promoting learning in a playful way. In this context, classic game mechanics can be powerful allies in the educational process. Objective: This paper presents BomberKaboom, an educational digital game designed to raise players’ awareness of environmental issues, such as wildfires and urban pollution, through mechanics inspired by the classic Bomberman. Methodology: The game was developed using the Unity engine with pixel art style, incorporating pedagogical goals related to environmental education. The system was evaluated by Computer Science students, who played the game and completed a questionnaire addressing usability, engagement, and thematic perception. Results: Participants reported high engagement and highlighted the game’s educational potential. The playful approach was considered effective in addressing environmental themes, and the retro aesthetic was well received. The findings suggest that games with familiar mechanics can facilitate the assimilation of important content and foster meaningful learning experiences.